The Need for Micro or Takaful in Islamic Insurance Partnerships in the Philippines - M. Radiamoda, Anwar (IKONOMIKA, 2025)
The study evaluates the feasibility of implementing affordable micro-Takaful solutions that align with Islamic finance principles to improve financial security for vulnerable groups. Findings indicate significant demand for Micro/Takaful in the Philippines, particularly among Muslim and low-income communities who face cultural and financial barriers to accessing conventional insurance. Micro-Takaful offers a Shari'ah-compliant, cost-effective alternative that fosters financial protection and mutual support. By promoting shared responsibility, it provides ethical insurance that aligns with Islamic values and has the potential to enhance social welfare, financial inclusion, and sustainability. The research highlights the importance of partnerships between Islamic financial institutions, local communities, and government entities to expand Micro/Takaful, ultimately improving financial security for underserved populations. With a growing Muslim population, the Philippines stands to benefit from this ethical model to meet the insurance needs of low-income communities.